EVALUATION OF THE EFFECTIVENESS OF COMPLEX TREATMENT OF PATIENTS WITH GENERALIZED PERIODONTITIS - Semenov, Ye.I.; Sennikov, O.M.; Kotelevskyi, R.A.; Skulska, S.V.; Vyshnevska, H.O.; Rozhko, S.M.; Sapalov, S.O. (World of Medicine and Biology, 2023)
The study was devoted to evaluating the complex treatment of generalized periodontitis, as well as the dynamics of changes in periodontal tissues after its completion. In total, 15 patients aged 30–55 were examined with the periodontal probing system to monitor the treatment measures taken at the end of conservative treatment of symptomatic gingivitis. Of these, 15 patients were examined approximately after 8–9 months from start of the treatment and 11 patients were examined approximately 2 years from start of the treatment. Treatment results indicated higher effectiveness on the lower jaw with a reduction in epithelial attachment depth by 23.8±4.6 % 6–8 months post-treatment, compared to 9.1±1.6 % on the upper jaw. The therapeutic effects were found to be persistent even 2 years after treatment completion